Finding Value in Diversity: Verification of Personal and Social Self-Views in Diverse Groups - Swann, William B.; Polzer, Jeffrey T.; Seyle, D. Conor; Ko, Sei Jin (Academy of Management Review, 2004)
William B. Swann Jr., Jeffrey T. Polzer, Daniel Conor Seyle, Sei Jin Ko, Finding Value in Diversity: Verification of Personal and Social Self-Views in Diverse Groups, The Academy of Management Review, Vol. 29, No. 1 (Jan., 2004), pp. 9-27